Efl learner’s motivation and attitude toward English language learning at the “Technical University of Cotopaxi” - Espín Vásconez, Elly Rachel (2022)
Motivation is an important element in language learning. The main objective is to determine the EFL learners’ motivation and attitude towards English language learning at the “Technical University of Cotopaxi”. This present project has a quantitative approach and a descriptive method. Besides, a survey was chosen by the researchers to use it as the preferred data collection technique. The survey that was applied is an adaptation from the Gardner`s Attitude Motivation Test Battery (AMTB), which measures the level of motivation that students have. In this sense, the survey was directly carried out to 1975 students from which a randomly sample was carried out to 322 students at the Languages Center of "La Matriz" campus in the Technical University of Cotopaxi. The elicited final results from this research show that there is a high percentage of integrative motivation with 62.73%, meanwhile, instrumental motivation has 21,74%. On the other hand, according to the obtained results, the dominant type of motivation among participants is integrative with 62,73%. It’s worth mentioning that motivation in foreign language learning plays a meaningful role which ultimately influence on learners' commitment level towards overcome acquisition barriers of a new language.